Pelatihan Pembuatan Curriculum Vitae Menggunakan Kinobi CV sebagai Pengembangan Keterampilan Profesional Siswa MA As-Shofa Jubung: Pengabdian - Alifah, Dia Ayu Nur; Hardjati, Susi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the understanding and skills of Madrasah Aliyah (MA) As-Shofa Jubung students in creating professional digital-based Curriculum Vitae (CV) using the Kinobi platform. The training was conducted on August 2, 2025, using a participatory approach through three main stages: material presentation, hands-on practice, and evaluation. Interactive lectures, tutorials, and discussions were implemented to help participants comprehend and apply the concept of ATS-friendly CVs independently. During the session, students were introduced to the structure and components of a professional CV according to industry standards and guided in creating their own CVs through Kinobi’s features. The results revealed that students showed high enthusiasm and significant improvement in composing professional CVs. Based on feedback surveys, most participants agreed that the program enhanced their career literacy, understanding of the Applicant Tracking System (ATS), and ability to manage professional digital profiles. This training had a positive impact in fostering career readiness and raising early awareness of personal branding among MA As-Shofa Jubung students.